The Principles of Sustainability in Economics and the War in Europe - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2022)
Can we talk about “community hegemony” when we talk about choosing or removing a government leadership as in the case of Russian dictatorship and of tragic and terrible war in Ukraine? The Russian people, literally bombarded with fake news and manipulations of reality about war (directly coming from the old Soviet “dezinformatzija" дезинформация), may seem completely bewitched by censorship. Nevertheless, we must believe that the responsibilities always entrusted to the community in terms of life and choice freedom can never be completely extinguished. As saying that the longing for the freedoms guaranteed by democracy has been part of the DNA of Earth peoples starting from birth. For this reason, the possibility of removing the dictatorship in Russia lies with the community, although the conditions are not yet favorable for a democratic power alternation in Russia. Therefore, this is the real final goal that the Western countries must set, by continuing to support the defense of brave Ukrainian people by providing money and weapons. All the more true if we believe that the final goal of humankind is to ban the war and above all to dismiss even just the simple eventuality of an atomic war; which would only bring the destruction of life on Earth, This is in contrast to the goal that all living beings have in concert with nature, that is, the preservation of life on Earth. In my opinion, it’s therefore necessary that the great democracies take the common decision to remove the atomic arsenals from the control of leaders of those countries in possession of nuclear weapons and then entrust the whole nuclear arsenal to a global supranational authority, that would keep the atomic weapons in a “new Fort Knox” and later would dispose for their progressive reuse, but for peace purposes.